Exploring the Therapeutic and Gut Microbiota-Modulating Effects of Qingreliangxuefang on IMQ-Induced Psoriasis - Yu Z; Wang Y; Guo Y; Zhu R; Fang Y; Yao Q; Fu H; Zhou A; Ma L; Shou Q (Drug Design, Development and Therapy)
Zhengyao Yu,1– 5,* Yingying Wang,2,3,6,* Yingxue Guo,2,3,6 Ruotong Zhu,1,4 Yimiao Fang,1 Qinghua Yao,7 Huiying Fu,2,3,5,6 Ang Zhou,8 Lili Ma,1 Qiyang Shou2,3,5,6 1The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Traditional Chinese Medicine), Hangzhou, Zhejiang, 310006, People’s Republic of China; 2The Second School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 3Jinhua Academy, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 4The First School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 5Yongkang Hospital of Traditional Chinese Medicine, Jinhua, Zhejiang, 321300, People’s Republic of China; 6School of Pharmaceutical Sciences, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China; 7The Second Affiliated Hospital of Zhejiang Chinese Medical University, Xinhua Hospital of Zhejiang Province, Hangzhou, Zhejiang, 310005, People’s Republic of China; 8Department of Dermatology, Yiwu Central Hospital Medical Community Choujiang Hospital District, Yiwu, Zhejiang, 322000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lili Ma, The First Affiliated Hospital of Zhejiang Chinese Medical University (Zhejiang Provincial Hospital of Traditional Chinese Medicine), Hangzhou, Zhejiang, 310006, People’s Republic of China, Email lilyma163@163.com Qiyang Shou, The Second School of Clinical Medicine, Zhejiang Chinese Medical University, Hangzhou, Zhejiang, 310053, People’s Republic of China, Email sqy133@126.comPurpose: To investigate the therapeutic and gut microbiota-modulating effects of Qingreliangxuefang (QRLXF) on psoriasis.Materials and Methods: We used network pharmacology, a computational approach, to identify key bioactive compounds and biological targets, and explored the molecular mechanisms of QRLXF. The effects of QRLXF on keratinocyte proliferation and inflammation were evaluated using a mouse model of psoriasis. Changes in the gut microbiota were analyzed via 16SrDNA sequencing, and T cell subsets were assessed using flow cytometry.Results: Network pharmacology analysis suggested that QRLXF ameliorated psoriasis by modulating Th17 cell differentiation. Further experiments confirmed the anti-inflammatory effects and relief of psoriatic lesions in IMQ-induced mice. 16SrDNA sequencing revealed significant shifts in the gut microbiota, notably increases in Ligilactobacillus and Lactobacillus genera and decreases in Anaerotruncus, Negativibacillus, Bilophila, and Mucispirillum, suggesting a potential relationship between specific microbiota changes and Th17 cell differentiation.Conclusion: QRLXF alleviated psoriatic dermatitis by regulating Th17 cell responses and modifying gut microbiota profiles, highlighting its therapeutic potential for psoriasis treatment.Plain Language Summary: Psoriasis affects millions globally. We studied a traditional herbal formula, Qingreliangxuefang (QRLXF), for its potential in treating psoriasis. Using computer tools, we found QRLXF may control Th17 cells, which play a role in psoriasis. Testing QRLXF in mice with psoriasis-like skin issues showed reduced inflammation and improved skin appearance. Gut bacteria analysis revealed more beneficial bacteria like Ligilactobacillus and Lactobacillus and fewer harmful ones. Our findings suggest QRLXF could be a promising new treatment option for psoriasis. Keywords: psoriasis, QRLXF, T cell differentiation, 16SrDNA sequencing, Th17 cell responses